2020
DOI: 10.1021/acs.iecr.9b06683
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up of a Rotating Packed Bed Reactor with a Mesh-Pin Rotor: (I) Hydrodynamic Studies

Abstract: The rotating packed bed (RPB) reactor with a lab-scale mesh-pin rotor (MPR) displays the great potential for the chemical processes with viscosity reactants or solid products. However, the scale-up research of the RPB reactor with MPR needs to be taken into consideration, which is the foundation for pilot-scale and industrial application. In this work, the scale-up principles of MPR were proposed for the first time, and the hydrodynamic study was conducted by using a high-speed camera. The liquid flow patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
2
16
0
2
Order By: Relevance
“…•wire mesh packing produced stronger shear stress and smaller droplets, compared to nickel foam packing 29,30 experimental, high-speed camera •liquid flow pattern, impaction−disintegration modes of droplet−packing interactions, droplet velocity, and size were investigated…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…•wire mesh packing produced stronger shear stress and smaller droplets, compared to nickel foam packing 29,30 experimental, high-speed camera •liquid flow pattern, impaction−disintegration modes of droplet−packing interactions, droplet velocity, and size were investigated…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamics of RPBs can be studied using experimental and modeling methods. In Table , some of the recent experimental and modeling research on the study of the hydrodynamics of RPBs are reported. As can be observed in Table , experimental methods in the study of the hydrodynamics of RPBs mainly include sampling from the inlet and outlet gas and liquid streams, high-speed camera, and X-ray computed tomography (CT) scanning. ,,, Two main approaches have been generally utilized in the literature on the modeling side: compartmental modeling and computational fluid dynamics (CFD). In compartmental modeling, the reactor is divided into different zones and in each zone, the equations of conservation for mass and energy, coupled with equations for interphase heat and mass transfer, are solved .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [13] 62.832 3.095 1.004 0.0727 0.18 999 0.172 0.5014 44 Liu et al [13] 83.776 3.095 1.004 0.0727 0.18 999 0.172 0.3812 45 Liu et al [13] 104.72 3.095 1.004 0.0727 0.18 999 0.172 0.3263 46 Liu et al [13] 125.66 [18] 94.25 1.965 1.12 0.0731 0.22 999 0.2305 0.5614 76 Sang et al [18] 115.192 1.965 1.12 0.0731 0.22 999 0.2305 0.5182 77 Sang et al [18] 52.36 1.965 1.12 0.0387 0.22 999 0.2305 0.7174 78 Sang et al [18] 73.304 1.965 1.12 0.0387 0.22 999 0.2305 0.6065 79 Sang et al [18] 94.248 1.965 1.12 0.0387 0.22 999 0.2305 0.5152 80 Sang et al [18] 115.192 1.965 1.12 0.0387 0.22 999 0.2305 0.4848 81 Sang et al [18] 52.36 1.965 1.12 0.0731 0.22 999 0.2505 0.7260 82 Sang et al [18] 52.36 1.965 1.12 0.0731 0.22 999 0.2705 0.7272 83 Sang et al [18] 52.36 1.965 1.12 0.0731 0.22 999 0.2905 0.6046 84 Sang et al [18] 52.36 1.965 1.12 0.0731 0.22 999 0.3105 0.5745 85 Sang et al [18] 94.248…”
Section: Vof Modelunclassified
“…This is in part caused by the small size (O [100 μm]) and a large number of droplets inside the bed. [13,15,17] The number and size of droplets dictate the mass transfer area in the bed. Researchers have used experimental and simulation methods to measure the droplet size in RPBs.…”
mentioning
confidence: 99%
See 1 more Smart Citation